Helpful viability of post calving tonic for the treatment of post calving complications in dairy animals (Journal of Advanced Veterinary and Animal Research, 2021)
Objectives: Aimless use of anti-microbials for the treatment of uterine diseases has driven the rise of safe strains. Subsequently, within the current consider, the viability of post calving tonic (PCT) was assessed in vivo for the treatment of post calving complications in dairy cattle.  Materials and Methods: The placentas of 10 chosen post-calved dairy animals with a history of postpartum complications primarily held placentas were drenched with PCT 250 ml twice a day for 2 successive days. The evaluation parameters, viz., time taken for removal of lochia, placenta, involution of the uterus and estrus come back time, body condition score, and milk yield have been analyzed to assess the efficacy of PCT in post calved dairy bovines.  Results: The results depicted that following the administration of PCT, the mean time taken for expulsion of uterine discharge (lochia), placenta, time taken for the involution of the uterus, and estrus come back time was 86 and 10 h, 30 and 36 days, respectively. Additionally, the administration of PCT 250 ml twice daily for 2 consecutive days to the post-calved dairy cows caused a significant increase (p < 0.05) in milk yield.  Conclusion: It was apparent that PCT encourages the unconstrained removal of held placenta through its ecbolic movement and advances uterine discharge exercises. In addition, PCT supplementation caused augmentation of milk yield in post calved dairy cows.J. Adv. Vet. Anim. Res., 8(4): 650–655, December 2021http://doi.org/10.5455/javar.2021.h557